Reconnecting society with its ecological roots. Issue 116 (February 2021) - Everard, Mark; Kass, Gary; Longhurst, James; zu Ermgassen, Sophus; Girardet, Herbert; Stewart-Evans, James; Wentworth, Jonathan; Austin, Kevin; Dwyer, Ciara; Fish, Robert; Johnston, Paul; Mantle, Gary; et al.
Highlights: Ecosystem services and processes play key, if overlooked, roles in all policy areas. Realising the values of ecosystems requires embedding across all societal interests. Collaborative learning amongst senior players helped identify actionable outcomes. All sectors of society are key role players in achieving this society-wide transformation. Exemplar ecosystem-based approaches show the feasibility of societal transformation. Abstract: Recent high-profile analyses of trajectories and prognoses of ecosystem decline around the world have called for a renewed focus on embedding the values of the natural world across all areas of public policy. This paper reports the results of a UK-based deliberative process involving experts from a wide range of policy domains and across societal sectors: government departments, associated agencies, national and international NGOs, professional institutions, academia and independent experts. A symposium, based on a collaborative learning approach, explored instances in which ecosystem values have successfully been embedded into public policy, identified challenges to their more widespread embedding despite commitments to do so over generational timescales, and took a backcasting approach to develop actionable outcomes required to deliver transformation change across state and civil society. Emergent themes were expressed in social, technological, environmental, economic and political terms. Recommendations for interventions in complex social-ecological systems are cross-sectoral in scope and will necessarily entail multiple agents of change, well beyond governmental leadership, within any given sphere of societal activity and interest. We identify strategic challenges for, and between, a spectrum of societal policy areas, many currently overlooking ecosystem dependencies, impacts and potential benefits. Reflections on the collaborative learning approach are also provided.